2022
DOI: 10.3389/fenvs.2022.966580
|View full text |Cite
|
Sign up to set email alerts
|

Environmental information disclosure and green energy efficiency: A spatial econometric analysis of 113 prefecture-level cities in China

Abstract: As one of the means of informal environmental regulation, environmental information disclosure has an essential impact on improving green energy efficiency. This paper selects the panel data of 113 environmental information disclosure cities in China from 2008 to 2018 and uses the Super-efficiency SBM model with undesirable outputs to measure green energy efficiency. Based on the measurement results, this paper empirically studies the impact of environmental information disclosure on green energy efficiency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The three dimensions of information transparency are product transparency, supply chain transparency, and transaction transparency (Zhou et al, 2018). Studies of information transparency focus on information disclosure in capital markets (Zadeh et al, 2021), information sharing in supply chains (Rao et al, 2021), corporate social responsibility disclosure (Sendlhofer and Tolstoy, 2022), environmental information disclosure (Teubner et al, 2020;Du et al, 2022;Lin, 2022), and product information disclosure (Peschel and Aschemann-Witzel, 2020).…”
Section: Signaling Theorymentioning
confidence: 99%
“…The three dimensions of information transparency are product transparency, supply chain transparency, and transaction transparency (Zhou et al, 2018). Studies of information transparency focus on information disclosure in capital markets (Zadeh et al, 2021), information sharing in supply chains (Rao et al, 2021), corporate social responsibility disclosure (Sendlhofer and Tolstoy, 2022), environmental information disclosure (Teubner et al, 2020;Du et al, 2022;Lin, 2022), and product information disclosure (Peschel and Aschemann-Witzel, 2020).…”
Section: Signaling Theorymentioning
confidence: 99%
“…Developed countries with strict environmental regulations tend to develop clean industries and shift pollution-intensive industries to developing countries through foreign direct investment (Wang et al, 2020), and FDI in China has shown more scale and structural effects than technology effects which could compensate for the environmental pollution. The positive indirect effect of FDI in column (5) could result from a "learning effect" in regional policy decision (Du et al, 2022), cities with lenient environmental policies can attract more foreign investment and are more likely to achieve the target of political performance such as GDP.…”
Section: Estimation Resultsmentioning
confidence: 99%
“…Since many external factors affect EE, a set of provincial-level control variables are added to the benchmark model in this paper based on existing studies to mitigate the bias caused by missing variables as much as possible (Sun et al, 2019;Chien et al, 2021;Du et al, 2022;Wang et al, 2022d;Rasoulinezhad and Taghizadeh-Hesary, 2022). This set of inter-provincial characteristic variables includes regional economic development level (EDL), measured by the real per capita GDP, excluding the price factor.…”
Section: Control Variablesmentioning
confidence: 99%